Community-, facility-, and individual-level outcomes of a district mental healthcare plan in a low-resource setting in Nepal: A population-based evaluation - Jordans, Mark J. D. (PLoS Med, 2019)
BACKGROUND: In low-income countries, care for people with mental, neurological, and substance use (MNS) disorders is largely absent, especially in rural settings. To increase treatment coverage, integration of mental health services into community and primary healthcare settings is recommended. While this strategy is being rolled out globally, rigorous evaluation of outcomes at each stage of the service delivery pathway from detection to treatment initiation to individual outcomes of care has been missing. METHODS AND FINDINGS: A combination of methods were employed to evaluate the impact of a district mental healthcare plan for depression, psychosis, alcohol use disorder (AUD), and epilepsy as part of the Programme for Improving Mental Health Care (PRIME) in Chitwan District, Nepal. We evaluated 4 components of the service delivery pathway: (1) contact coverage of primary care mental health services, evaluated through a community study (N = 3,482 combined for all waves of community surveys) and through service utilisation data (N = 727); (2) detection of mental illness among participants presenting in primary care facilities, evaluated through a facility study (N = 3,627 combined for all waves of facility surveys); (3) initiation of minimally adequate treatment after diagnosis, evaluated through the same facility study; and (4) treatment outcomes of patients receiving primary-care-based mental health services, evaluated through cohort studies (total N = 449 depression, N = 137; AUD, N = 175; psychosis, N = 95; epilepsy, N = 42). The lack of structured diagnostic assessments (instead of screening tools), the relatively small sample size for some study components, and the uncontrolled nature of the study are among the limitations to be noted. All data collection took place between 15 January 2013 and 15 February 2017. Contact coverage increased 7.5% for AUD (from 0% at baseline), 12.2% for depression (from 0%), 11.7% for epilepsy (from 1.3%), and 50.2% for psychosis (from 3.2%) when using service utilisation data over 12 months; community survey results did not reveal significant changes over time. Health worker detection of depression increased by 15.7% (from 8.9% to 24.6%) 6 months after training, and 10.3% (from 8.9% to 19.2%) 24 months after training; for AUD the increase was 58.9% (from 1.1% to 60.0%) and 11.0% (from 1.1% to 12.1%) for 6 months and 24 months, respectively. Provision of minimally adequate treatment subsequent to diagnosis for depression was 93.9% at 6 months and 66.7% at 24 months; for AUD these values were 95.1% and 75.0%, respectively. Changes in treatment outcomes demonstrated small to moderate effect sizes (9.7-point reduction [d = 0.34] in AUD symptoms, 6.4-point reduction [d = 0.43] in psychosis symptoms, 7.2-point reduction [d = 0.58] in depression symptoms) at 12 months post-treatment. CONCLUSIONS: These combined results make a promising case for the feasibility and impact of community- and primary-care-based services delivered through an integrated district mental healthcare plan in reducing the treatment gap and increasing effective coverage for MNS disorders. While the integrated mental healthcare approach does lead to apparent benefits in most of the outcome metrics, there are still significant areas that require further attention (e.g., no change in community-level contact coverage, attrition in AUD detection rates over time, and relatively low detection rates for depression).